Impacts of prolonged chlorpyrifos exposure on locomotion and slow-and fast- twitch skeletal muscles contractility in rats. (2019) - Hallal, Nancy; El Khayat El Sabbouri, Hiba; Salami, Ali; Ramadan, Wiam; Khachfe, Hassan; Moustafa, Mohamed E.; Khalil, Mahmoud; Joumaa, Wissam H.
Highlights: Prolonged exposure to chlorpyrifos induced locomotor impairments. Chlorpyrifos exposure modified the characteristics of twitch contraction of mammalian skeletal muscle fibers. Structural and functional alterations are reported as adaptation of the fibers muscle to chlorpyrifos exposure. Abstract: Aim: Investigate the effect of dietary exposure to chlorpyrifos on locomotion and contraction of soleus and extensor digitorum longus ( edl ) involved in locomotion. Methods: Rats were fed diets containing 1 or 5 mg kg −1 of chlorpyrifos for six weeks. Locomotion has been assessed weekly using beam walking and beam balance tests. Soleus and edl were removed to study contractile properties, myofibrillar protein content and myosin heavy chain isoforms. Results: Animals treated with 5 mg kg −1 chlorpyrifos had a decrease body weight. An increase by 28% and 24% in latency time assessed by beam walking test and a decrease by 9% and 13% in the beam balance time was reported after 6 weeks of 1 and 5 chlorpyrifos exposure respectively. The contractile properties in soleus showed an increase in twitch amplitude by 25% and 63% in 1 and 5 doses respectively, without modification in the contraction time and half relaxation time. edl treated with 1 mg kg −1 showed a decrease by 35%, 42% and 22% in twitch amplitude, contraction time and half relaxation time respectively. edl treated with 5 mg kg −1 showed an increase of 23% in twitch amplitude without modification of the other parameters. These changes were associated with modification of myofibrillar protein content in all treated groups. Myosin heavy chain isoforms were altered in both skeletal muscles treated with 1 mg kg −1 . Conclusion: Exposure to chlorpyrifos can alter the locomotion and produce physiological changes in a dose and muscle type related manner.